PENGARUH LIKUIDITAS TERHADAP RETURN SAHAM : PENGUJIAN BERBAGAI PROKSI LIKUIDITAS - , Chorry Sulistyowati, SE.; , Dr. Erni Ekawati, MBA., MSA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aimed to empirically test the impact of liquidity to stock return in two stock groups with different liquidity level. First group consist of the highest stock liquidity. In the other hand, last group is the most illiquid companies. Data used in this research are taken from Indonesia Stock Market from January 2005 until December 2009. Frequency data monthly, totally there are sixty month observations. Five proxies from trade based measures and two proxies from order based measures are used in this research. Seven variables non relative and seven variable relative are implemented. Two hypothesises are obligated. First, what is the dominant liqudity proxy in Indonesia and which one is better relative measures or not relative The result explained that liquidity has positively impact in the most liquid company but negative in the least liquid stock group. The first hypothesis can not answered because of the researcher can not get the same sample after stock sorting depend on seven proxies namely volume, value, frequency, turnover, illiquidity, spread and spread per price. Relative Market Liquidity Turnover or RML TURN is the only relative proxy that negatively significant impact stock return in the least liquid stocks.